Simulation analysis of graphene addition on polymeric composite - Nisa Naima Khalid; Nabilah Afiqah Mohd Radzuan; Abu Bakar Sulong; Farhana Mohd Foudzi; Mihirssen Gunasegran (Penerbit Universiti Kebangsaan Malaysia, 2022)
Natural fibres in composite materials, such as kenaf fibres, are used to reinforce polypropylene (PP) due to their light weight and high mechanical performance required in various applications, such as automotive. Although natural fibres seem to be the most promising material, manufacturing parameters and material composition are crucial to determining balanced output performance. Therefore, this study provides essential knowledge on defining the parameters and the effect of addition of graphene content to kenaf fibres composites using computer simulation via Abaqus CAE software. Detailed analyses were compared with the experimental data of Young’s modulus and tensile strength. General static and dynamic explicit analyses were conducted using Abaqus CAE simulations, and set at 40 wt. % kenaf fibres, 0, 1, 3, and 5 wt. % graphene. Short kenaf fibres were utilised together with graphene nanoplatelets and prepared using a hot-pressing technique with the temperature set at 190 °C and pressure of 5 MPa for 5 min. The findings indicated that the simulation and experimental data from previous studies data congruent which is Young’s modulus and tensile strength increased with addition of graphene content. Thus, the simulated data could predict the experimental mechanical performance, in which 24 MPa of tensile strength was recorded for 3 wt. % of graphene additions.